2022
DOI: 10.1021/acsnano.1c11264
|View full text |Cite
|
Sign up to set email alerts
|

Subnanometer Ion Channel Anion Exchange Membranes Having a Rigid Benzimidazole Structure for Selective Anion Separation

Abstract: Ion-conductive polymers having a well-defined phase-separated structure show the potential application of separating mono- and bivalent ion separation. In this work, three side-chain-type poly­(arylene ether sulfone)-based anion exchange membranes (AEMs) have been fabricated to investigate the effect of the stiffness of the polymer backbone within AEMs on the Cl–/NO3 – and Cl–/SO4 2– separation performance. Our investigations via small-angle X-ray scattering (SAXS), positron annihilation, and differential scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 74 publications
(114 reference statements)
1
26
0
Order By: Relevance
“…In the literature, there are a number of studies aimed at increasing the selectivity of IEMs in relation to the counterion transport both by synthesizing new membranes [ 19 , 20 ] and by modifying commercially available ones [ 21 , 22 , 23 , 24 ]. Attempts to increase selectivity often lead to a decrease in IEM conductivity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are a number of studies aimed at increasing the selectivity of IEMs in relation to the counterion transport both by synthesizing new membranes [ 19 , 20 ] and by modifying commercially available ones [ 21 , 22 , 23 , 24 ]. Attempts to increase selectivity often lead to a decrease in IEM conductivity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the approaches mentioned above, the hydrophilic–hydrophobic balance was controlled either by varying the length of the alkyl group attached to the quaternary ammonium moiety or by increasing the alkyl chain length of the spacer used for cross-linking. ,, Another way to achieve maximum P SO 4 2– Cl – is by controlling the size of the ion sieve in the membrane matrix . Herein, our approach is to control the size of the ion channel and water content or hydrophilic–hydrophobic balance in the membrane by partial quaternization of a copolymer followed by cross-linking using another functional copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…. 33 Irfan et al prepared a series of MASMs by mixing bromomethylated polyphenylene oxide with tertiary amines containing different alkyl chain lengths that show a P SOd 4 2− Cld − value of 13.07. 27 Liao et al prepared MASMs by introducing both the cationic and anionic groups in the membrane surface based on a long alkyl chain imidazole functionalized polymer followed by cross-linking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the feasibility of our proposal set forth in Figure , functionalized Pi-POSS was prepared through decorating POSS nanoparticles with N -methylpiperidium groups, which were demonstrated to possess distinguished resistance against nucleophilic substitution and elimination under high temperatures and alkaline conditions. AEMs consist of the hydrophobic polymer backbone and hydrophilic cationic groups, which directly determine the dimensional stability, alkaline stability, and ion conductivity of AEMs. To improve the durability under alkaline conditions of AEMs, numerous studies on cationic groups and polymer backbones have been carried out. , Marino et al systematically investigated the alkaline stability of different kinds of quaternary ammonium (QA) groups . The results showed that the piperidinium-based cation certificates strong resistance against nucleophilic substitution and elimination under high temperatures and alkaline conditions …”
Section: Introductionmentioning
confidence: 99%